2018
DOI: 10.1007/s11205-018-1865-8
|View full text |Cite
|
Sign up to set email alerts
|

A Delphi Approach to Develop Sustainable Food System Metrics

Abstract: Recurrent food crises and global environmental change are critical issues that pushed food security and sustainability to the top of the policy agenda. Policy-makers need assessment tools that help them decide what actions they should take to achieve these goals. This paper proposes a new metric system assessing the sustainability of food systems and diets at a subnational level adapted to the context of the Mediterranean area. Recognizing the systemic dimension of sustainability, the proposed information syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 67 publications
0
61
0
3
Order By: Relevance
“…Important exceptions in this regard are provided by recent efforts to analyze concrete food system interactions(Kopainski et al, 2018) and develop metrics that can capture them(Allen at al., 2018). Also relevant is Kopainski et al s (2017) work with small farmers in Zambia to adapt participatory system dynamics modeling at the community level and support local capacitybuilding and decision-making in relation to food security.…”
mentioning
confidence: 99%
“…Important exceptions in this regard are provided by recent efforts to analyze concrete food system interactions(Kopainski et al, 2018) and develop metrics that can capture them(Allen at al., 2018). Also relevant is Kopainski et al s (2017) work with small farmers in Zambia to adapt participatory system dynamics modeling at the community level and support local capacitybuilding and decision-making in relation to food security.…”
mentioning
confidence: 99%
“…However, the complexity of farming-activity forces to the adoption of a holistic approach to sustainability assessment [26]. There are tools that assess sustainability, understood as the ability of a system to maintain and improve its essential functions over time [27,28]. In this study, we selected the Framework for Assessing the Sustainability of Natural Resource Management Systems (MESMIS, the acronym in Spanish) [29] to evaluate the impact of FFSs on the sustainability and FNS of mountain peasant-farming systems.…”
Section: Methodological Framework and Data Collectionmentioning
confidence: 99%
“…The MESMIS is a systemic framework that, unlike those used by other authors such as Allen [28], highlights the bottom-up approach. In our study, the indicators were agreed with the specialist team and with the farmers.…”
Section: Methodological Framework and Data Collectionmentioning
confidence: 99%
“…These tools encourage the behavioural change of producers and consumers towards long-term sustainability and allow selecting products and services according to specific environmental and social criteria. Eco-labels are acknowledged to contribute to the resilience of local food systems to environmental loss (Allen et al 2019). In our case study analysis-according to de Haes et al's classification (de Haes et al 2010)-we have identified in the market two eco-labelling schemes related to sustainability certifications of natural resources and to regional products: (i) sustainability certifications that function as marketing tools, protecting and improving the value of the brand or supermarket chain; (ii) regional products that stem from a well identifiable region, referring to various quality aspects, to a focus on gastronomy, to traditional techniques, and to the employment of human resources (also attention for the environment is more and more associated with regional products).…”
Section: Eco-labelsmentioning
confidence: 99%